The Relationship between High Heel Size Variation and Long Standing Duration on the Risk of Plantar Fasciitis - Mochamad Fikri Alfredo Brian Rahma; Peppy Nawangsasi; Eka Poerwanto; Adi Suriyanto (Indonesian Journal of Global Health Research, 2026)
a Plantar fasciitis is one of the most common musculoskeletal complaints, especially in working women who often wear high heels and stand for long periods of time, such as Sales Promotion Girl (SPG). Biomechanical stress due to unnatural foot position when wearing high heels and standing static for long periods of time can increase the risk of plantar fasciitis. This study aimed to determine the relationship between the variation in the size of high heels and the length of standing duration on the risk of plantar fasciitis in female Sales Promotion Girl (SPG) workers. A cross-sectional study was conducted in one of the shopping centers in Surabaya in June 2025 - September 2025. A total of 66 Sales Promotion Girls were selected by simple random sampling. The dependent variable is plantar fasciitis. Independent variables were variations in heel size, high heel, and length of standing. Data was collected using questionnaire that had been tested for validity and reliability. The data was analyzed by the Spearman Correlation Test. The results showed that 68.6% of respondents used ≥5 cm heels and 57.1% stood >8 hours per day. Of all respondents, 51.4% experienced no pain, 32.9% mild pain, and 15.7% moderate pain. Spearman's correlation analysis found a moderately positive association between high heel shoe height and standing duration with the risk of plantar fasciitis (p<0.001). The variation in the size of high heels and long standing duration had a significant relationship with the risk of plantar fasciitis, with a positive relationship, namely the higher the heel and the longer the duration of standing, the higher the risk of SPG women experiencing plantar fasciitis.